CEACAM 1, 3, 5 and 6 -positive classical monocytes correlate with interstitial lung disease in early systemic sclerosis - Yokoyama, Kana; Mitoma, Hiroki; Kawano, Shotaro; Yamauchi, Yusuke; Wang, Qiaolei; Ayano, Masahiro; Kimoto, Yasutaka; Ono, Nobuyuki; Arinobu, Yojiro; Akashi, Koichi; Horiuchi, Takahiko; Niiro, Hiroaki (Frontiers in Immunology, 2022)
Background: Systemic sclerosis (SSc) is a multiple-organ disease characterized by vascular damage, autoimmunity, and tissue fibrosis. Organ injuries such as interstitial lung diseases (ILD), resulting from inflammatory and fibrosis processes, lead to poor prognosis. Although autoantibodies are detected in the serum of patients with SSc, the mechanisms by which immune cells are involved in tissue inflammation and fibrosis is not fully understood. Recent studies have revealed carcinoembryonic antigen related cell adhesion molecule (CEACAM)-positive monocytes are involved in murine bleomycin-induced lung fibrosis. We investigated CEACAM-positive monocytes in patients with SSc to clarify the role of monocytes in the pathogenesis of SSc. Methods: The proportion of of CEACAM-positive classical monocytes in healthy controls (HCs) and patients with rheumatoid arthritis (RA) and SSc was evaluated using flowcytometry. The correlation between the proportion of CEACAM-positive monocytes and clinical parameters was analyzed in patients with SSc. Gene expression microarrays were performed in CEACAM-positive and negative monocytes in patients with SSc. Infiltration of CEACAM-positive monocytes into scleroderma skin was evaluated by immunohistochemical staining. Results: The proportion of CEACAM-positive classical monocytes was increased in patients with early SSc within 2 years after diagnosis, which positively correlated with ESR, serum IgG, and serum KL-6 and negatively correlated with %forced vital capacity. The percentage of CEACAM-positive monocytes decreased after immunosuppressive therapy. CEACAM6-positive cells among classical monocytes were significantly increased in patients with SSc compared with HCs and patients with rheumatoid arthritis. SSc serum induced CEACAM6 expression on monocytes from HCs. Functionally, CEACAM-positive monocytes produced higher levels of TNF-α and IL-1β compared to CEACAM-negative cells and showed activation of the NF-κB pathway. Furthermore, CEACAM6-positive monocytes infiltrated the dermis of SSc. Conclusions: CEACAM-positive monocytes showed inflammatory phenotypes and may be involved in the tissue inflammation and fibrosis in early SSc. CEACAM-positive monocytes may be one of biomarkers to detect patients with progressive ILD, requiring therapeutic intervention.